KEBIJAKAN PEMERINTAH INDONESIA MERATIVIKASI PERJANJIAN EKSTRADISI DENGAN SINGAPURA TAHUN 2008-2012 - SANUR, RYANTI; Rani, Faisyal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research describes the Government of Indonesia policy to rativication extradition treaty with Singapore in 2008-2012. Extradition treaty are one of most intternational teraty that have function to keep and catch the corruptor that move money from Indonesia to Singapore to invest. Without extradition teraty the Government of Indonesia prohibited to jail the corruptor because that the extradition treaty are important classiffied for Indonesia to destroyed the corruption.The writer collects data from books, encyclopedia, journal, mass media and websites to analyze the Government of Indonesia policy to rativication extradition treaty with Singapore. The theories applied in this research are foregin policy decision theory from William D. Coplin and national interest concept from Donald. E. Nuchterlain and extradition concept in international law.The research shows that Government of Indonesia policy to rativication extradition treaty with Singapore are because the increase of corruption Indonesia that move the money from Indonesia to invest in Singapore and amandement content of extradition treaty between Indonesia and Singapore about the extradition treaty may the Government of Indonesia to take the corruptor from 15 years ago and extradition treaty also may to other criminal form likes robbery, blackmail or extortion by means of threats, kidnapping and any other offence which is made extraditable by the extradition laws of bothParties and laws enacted to give effect to obligations under an international convention to which both are parties.Key words: extradition, policy and treaty.